ANALISIS WEBQUAL 4.0 DAN IMPORTANCE-PERFORMANCE ANALYSIS E-LEARNING BDK MAKASSAR - Muh Zainal (Balai Diklat Keagamaan Bandung, 2022)
This study aims to determine the quality of the BDK Makassar e-Learning website and the level of conformity of BDK Makassar e-Learning to user needs using the webqual 4.0 and Importance-Performance Analysis (IPA) methods. This type of research is quantitative descriptive research using a questionnaire instrument to determine the Useability, Information and Service Interactio of the BDK Makassar e-learning website. Data analysis techniques use webqual and IPA analysis techniques. The results showed that the overall average value in each interest component was 3.83, while the overall average value on each performance component was 3.70 with a degree of conformity between the expectations of participants and widyaiswara with a performance level on the elements of performance and importance of 96.72%, as well as an average gap level of -0.466 which means that the BDK Makassar e-Learning website has a quality of service that does not meet the expectations of participants and Widyaiswara. The results of the IPA analysis show that the BDK Makassar e-Learning web is in quadrant I of the First Priority, especially in the Information Quality Element which is an important indicator but the performance displayed is low. In order for BDK Makassar e-Learning to be improved in quality, it is necessary to address the relevance of information (IQ 11) so that user expectations can be met.